Teaching Solar System Topic through Predict-Observe-Explain-Apply (POEA) Strategy: A Path to Students’ Conceptual Change - Supriatna, Ugi; Samsudin, Achmad; Efendi, Ridwan (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2019)
The misconception of the Solar System topic is still found in students so that it becomes one of the obstacles in the learning process. The purpose of this study is to analyze the effectiveness of the implementation of Predict-Observe-Explain-Apply (POEA) learning to change the junior high school students' conception in the Solar System topic. Quasi-experimental research with the non-equivalent control group design was conducted in one of the private junior high schools in Bandung city. Samples were selected based on the test of the average significance of the pretest score of the population. Furthermore, 30 students of the experimental class and 32 students of control class were selected. The research instrument, which consisted of 15 four-tier diagnostic test questions about Solar System were used to collect data before and after treatment. The tests were analyzed quantitatively by using the Mann-Whitney statistical test to determine the significance of the difference in the acceptable conception changes (Acceptable Change) of students in the experimental class with changes in the conception of students in the control class. The results of the research show that the implementation of POEA learning is significantly more effective than POE learning in changing the conception of Solar System topic. The findings of this study can be an alternative for junior high school teachers in planning learning about the Solar System, especially in an effort to change students' misconception about the Solar System.